Analysis of trade-offs/synergies in land use function changes in Bin County, China - Ning, Jing; Zhang, Huimei; Shi, Dongwei; Du, Guoming (Frontiers in Environmental Science, 2023)
Land-use function has become an important role in land change science. More attention should be given to multifunctional land to achieve land structure optimization and sustainable land use. This paper takes Bin County in Heilongjiang Province of China as the research area and investigates the spatiotemporal pattern and tradeoff synergistic relationship of land functions from 2000 to 2020. Land functions were quantitatively measured by the spatiotemporal method of statistical data, INVEST model, CASA, RUSLE and other models. The results showed that :(1) during 2000-2020, the production function showed an overall trend of enhancement. Living function remained enhanced except the southeast and the north. The water conservation function was weakened in most areas, while the carbon fixation function was strengthened in the southeast and weakened in the central and northern parts. Soil conservation function decreased first and then increased, and increased significantly in southwest. (2) There was a synergistic relationship between production and living functions, and a trade-offs relationship between ecology and production functions and ecology and living functions from 2000 to 2020. (3) The production function and living function are mainly coordinated in space, and the collaborative agglomeration types are mainly distributed in Tangfang Town, Manjing Town and other areas. The spatial distribution of trade-offs and synergies between ecological and productive functions and ecological and living functions was similar. The trade-off and agglomeration types were scattered, and the synergies were distributed in Binxi Town and Juren Town.